PENGARUH PEMAHAMAN MODERASI BERAGAMA TERHADAP SIKAP SOSIAL MAHASISWA PROGRAM STUDI AGAMA ISLAM - Syafruddin; Eddi Supriadi (Jurnal Riset dan Transformasi Pendidikan, 2026)
Religious moderation has become an important discourse in higher education as an effort to strengthen tolerance, inclusiveness, and harmonious social interaction in multicultural societies. However, the influence of students’ understanding of religious moderation on their social attitudes has not been widely examined empirically. This study aims to analyse the effect of understanding religious moderation on the social attitudes of students in the Islamic Religious Studies Program. The study employed a quantitative correlational approach involving 120 students selected through proportional random sampling. Data were collected using questionnaires measuring students’ understanding of religious moderation and social attitudes. Data analysis techniques included descriptive statistics, Pearson correlation, and simple linear regression. The results showed that students’ understanding of religious moderation was categorized as high, while their social attitudes were in the good category. Correlation analysis indicated a significant positive relationship between understanding religious moderation and students’ social attitudes (r = 0.682, p < 0.05). Regression analysis revealed that understanding religious moderation contributed 46.5% to the variance of students’ social attitudes. These findings imply that strengthening religious moderation literacy in higher education can positively shape students’ tolerance, empathy, cooperation, and respect for diversity. Therefore, universities need to integrate religious moderation values into academic and student development programs